2014
DOI: 10.1155/2014/306814
|View full text |Cite
|
Sign up to set email alerts
|

25-Gauge Microincision Vitrectomy to Treat Vitreoretinal Disease in Glaucomatous Eyes after Trabeculectomy

Abstract: Purpose. To determine the feasibility of using 25-gauge microincision vitrectomy surgery (25GMIVS) to treat vitreoretinal disease in glaucomatous eyes which have previously undergone trabeculectomy (TLE). Methods. A consecutive, interventional case series. We performed 25GMIVS in 15 glaucomatous eyes that had undergone TLE. Follow-up period was 11.5 months. Results. 25GMIVS was successfully used and led to improvement in visual acuity (P < 0.01). We performed 25GMIVS for proliferative diabetic retinopathy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Patients whose eyes were treated previously with a glaucoma filtering bleb or GDI and require additional surgery are at risk of losing appropriate IOP control if an incision is required over a functioning bleb or GDI 2. In a previous study of 25-gauge microincision vitrectomies to treat vitreoretinal disease in glaucomatous eyes after trabeculectomy, the insertion point of the cannula was shifted so as to avoid disturbing the conjunctiva adjacent to the filtering bleb 3. A few previous reports have described the utility of a temporal approach during vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients whose eyes were treated previously with a glaucoma filtering bleb or GDI and require additional surgery are at risk of losing appropriate IOP control if an incision is required over a functioning bleb or GDI 2. In a previous study of 25-gauge microincision vitrectomies to treat vitreoretinal disease in glaucomatous eyes after trabeculectomy, the insertion point of the cannula was shifted so as to avoid disturbing the conjunctiva adjacent to the filtering bleb 3. A few previous reports have described the utility of a temporal approach during vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…There was a case in 2007 that reported successful outcome of 25G PPV in familial amyloid polyneuropathy patients with filtering bleb [ 11 ]. Kunikata et al recently reported the stable results of 25G microincision vitrectomy in eyes that received trabeculectomy [ 7 ]. Therefore, the authors evaluated 23G PPV for vitreoretinal disease in eyes with prior trabeculectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 36 % of the subjects had open angle glaucoma for which trabeculectomy was performed, followed by 27 % with neovascular glaucoma. Kunikata et al reported 53 % neovascular glaucoma and 13 % open angle glaucoma cases, and Thompson et al, reported 57 % open angle glaucoma and 17 % angle closure glaucoma [ 4 , 7 ]. In the current study, 4 eyes (36 %) of the 11 subjects had epiretinal membrane and 3 eyes (27 %) of the 11 subjects had proliferative diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations